MAHSULOTLARNING SIFAT KO‘RSATKICHLARINI ANIQLASH VA SIFATINI BAHOLASH (HO‘L MEVALAR MISOLIDA) - Maxmonov, U.A. (SCIENCE and SOCIETY, 2023)
The most important thing that interests consumers is the quality of products. Every consumer wants to get a quality product. On the other hand, manufacturers are trying to produce a high-quality and competitive product that meets the requirements of consumers. This article provides information about the qualitative indicators of widely consumed fruit products and their identification, as well as about the equipment and methods used in this regard. The author’s opinions the also presented with suggestions and conclusions.